2010
DOI: 10.1242/jcs.060665
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-2, a component of the tight junction, forms a paracellular water channel

Abstract: SummaryWhether or not significant amounts of water pass the tight junction (TJ) of leaky epithelia is still unresolved, because it is difficult to separate transcellular water flux from TJ-controlled paracellular water flux. Using an approach without differentiating technically between the transcellular and paracellular route, we measured transepithelial water flux with and without selective molecular perturbation of the TJ to unequivocally attribute changes to the paracellular pathway. To this end, MDCK C7 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
340
2
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 373 publications
(363 citation statements)
references
References 59 publications
13
340
2
8
Order By: Relevance
“…The finding that cldn10b-based TJs are highly permeable to Na + and, to a lesser extent, are permeable to Mg 2+ is in good agreement with previous reports that cldn10b forms a paracellular channel for small cations with a preference for monovalent over divalent cations (7,8,11). Furthermore, it fits well with the observation that the absence of cldn10b from the TAL led to decreased paracellular Na + permeability in mice (12).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that cldn10b-based TJs are highly permeable to Na + and, to a lesser extent, are permeable to Mg 2+ is in good agreement with previous reports that cldn10b forms a paracellular channel for small cations with a preference for monovalent over divalent cations (7,8,11). Furthermore, it fits well with the observation that the absence of cldn10b from the TAL led to decreased paracellular Na + permeability in mice (12).…”
Section: Discussionsupporting
confidence: 92%
“…This spatial separation is important for renal ion homeostasis and its discovery improves our understanding of paracellular transport organization. (8,11). Mice lacking cldn10 in the TAL display reduced paracellular Na + selectivity and develop hypermagnesemia, hypocalciuria, and nephrocalcinosis (12), i.e., renal retention of divalent cations.…”
Section: Significancementioning
confidence: 99%
“…29 However, it is not clear whether ochratoxin A is specific for cldn-4, or whether it may also affect expression/localization of other barrier related proteins. It is puzzling that reduced expression of cldn-1 in keratinocytes did not show an effect on water barrier as measured by a modified Ussing chamber, 30 neither in human primary keratinocytes (siRNA mediated K D ; 83 C/-8% knockdown) nor in mouse keratinocytes isolated from Cldn-1 homozygous knock-out (KO) mice. 24 This was highly surprising, because Cldn-1 KO mice die within the first day of birth due to high transepidermal water loss.…”
Section: Tj Composition and Function In Healthy Skin (And Cultured Kementioning
confidence: 99%
“…Rosenthal et al previously have demonstrated that a putative paracellular water channel-claudin-2-mediates transepithelial water permeation in MDCK-II cells (3). We found that endogenous ILDR1 expression in MDCK-II cells was below the detection limit by immunoblotting or immunofluorescent labeling (Fig.…”
Section: Ildr1 Inhibits Transepithelial Water and Solute Permeabilitymentioning
confidence: 48%
“…Jorge Fischbarg noticed that the corneal endothelium retained over 60% of water permeability even when AQP1, the only aquaporin expressed by these cells, was knocked out by genetic deletion (2). Rosenthal et al have demonstrated that, in cultured renal epithelium expressing the claudin-2 protein, transepithelial water permeability was significantly higher than in cells without its expression (3). Using an optical microscopic approach, Spring and coworkers have directly measured the velocity of water flow across the tight junction and have ruled out the existence of any significant transjunctional water flow, at least for the bicellular TJ (bTJ) (4).…”
mentioning
confidence: 99%